2018
DOI: 10.1200/jco.2017.76.7871
|View full text |Cite
|
Sign up to set email alerts
|

Peripheral Neuropathy, Sensory Processing, and Balance in Survivors of Acute Lymphoblastic Leukemia

Abstract: Purpose To compare peripheral nervous system function and balance between adult survivors of childhood acute lymphoblastic leukemia (ALL) and matched controls and to determine associations between peripheral neuropathy (PN) and limitations in static balance, mobility, walking endurance, and quality of life (QoL) among survivors. Patients and Methods Three hundred sixty-five adult survivors of childhood ALL and 365 controls with no cancer history completed assessments of PN (modified Total Neuropathy Score [mTN… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
32
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 35 publications
(36 citation statements)
references
References 37 publications
(20 reference statements)
2
32
2
Order By: Relevance
“…Several studies investigated static postural control in cancer patients in response to neurotoxic treatments, applying quantitative center of pressure (COP) analyses using a force plate 3 10 . However, available data are heterogeneous as to the time point of COP analysis, and the investigation of risk or protective factors.…”
Section: Introductionmentioning
confidence: 99%
“…Several studies investigated static postural control in cancer patients in response to neurotoxic treatments, applying quantitative center of pressure (COP) analyses using a force plate 3 10 . However, available data are heterogeneous as to the time point of COP analysis, and the investigation of risk or protective factors.…”
Section: Introductionmentioning
confidence: 99%
“…Researchers investigating the relationship between increased postural sway and peripheral sensory neuropathy relied on various measures to assess the state of the peripheral sensory system, including subjective reports of sensory symptoms (e.g., severity of numbness/tingling, Functional Assessment of Cancer Therapy-Gynecologic Oncology Group-neurotoxicity (FACT&GOG-Ntx), and CIPN 20-item quality of life questionnaire (CIPN20)) [ 21 , 29 , 32 , 33 , 40 ], vibration perception threshold [ 29 , 40 ], and conduction studies of peripheral nerves [ 33 ]. Composite scores that combine subjective symptoms and objective measures of sensory signs and reflexes (e.g., modified Total Neuropathy Score (mTNS)) [ 24 , 41 ] were also used [ 33 ]. Zahiri et al 2019 identified a significant correlation between the ML sway and plantar vibration perception threshold in patients reporting feet numbness/tingling [ 29 ].…”
Section: Resultsmentioning
confidence: 99%
“…Both studies quantified a composite score of postural sway during six standing conditions and mTNS. Wampler et al found a significant association between the composite score and the mTNS score in a group of breast cancer patients, but Varedi et al studying a cohort of adult survivors of childhood acute lymphoblastic leukemia did not find the same association [ 24 , 41 ]. Although different measures of postural sway and neuropathy were used in these correlational studies, the majority support an association of excessive postural sway with peripheral sensory deficits.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In a recent study of long-term childhood ALL survivors [5], we examined the potential effect of peripheral neuropathy on static and dynamic measures of balance. As hypothesized, the level of peripheral neuropathy was associated with poorer performance on dynamic measures of mobility (i.e., Timed Up and Go test) and endurance (i.e., 6-Minute Walk test); however the level of peripheral neuropathy was not associated with sway values for maintaining an upright posture on a dynamic posturography device.…”
mentioning
confidence: 99%